2022
DOI: 10.3390/ejihpe12090093
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic and Digital Education Factors Are Associated to General Health, Coping Strategies, and Academic Outcomes of Undergraduate Students during the Post-Pandemic Period

Abstract: The COVID-19 pandemic suddenly and forever changed the lives of many undergraduate students around the globe, forcing them to switch to online learning while undergoing social confinement within their homes. It is now well-established that this prolonged period of uncertainty impacted students’ well-being, health, and academic achievement. However, how student-related factors, such as coping strategies as well as sociodemographic, contextual, and technological variables, are linked to digital education factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 54 publications
(65 reference statements)
0
7
0
Order By: Relevance
“…Currently, many companies have seen the great need to predict future changes in the management of human talent, therefore, one of their priority tasks is to redefine traditional roles and responsibilities, which allow increasing the internal health of the organization through the overall employee health (Pino et al, 2020;Wang et al, 2020;Lunde et al, 2022;Tinella et al, 2022;Bezuidenhout et al, 2023); to achieve this end, organizations must have the ability to discover competent people with leadership qualities that promote better results in their work environment, as well as the use of strategies and mechanisms to develop more love (Tijjang et al, 2023), commitment (Grabowski et al, 2019;Tacadena and Muico, 2022;Mitonga-Monga et al, 2023) and ethics (Grabowski et al, 2019;Sakr et al, 2022;Tacadena and Muico, 2022), from employees to your organization.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, many companies have seen the great need to predict future changes in the management of human talent, therefore, one of their priority tasks is to redefine traditional roles and responsibilities, which allow increasing the internal health of the organization through the overall employee health (Pino et al, 2020;Wang et al, 2020;Lunde et al, 2022;Tinella et al, 2022;Bezuidenhout et al, 2023); to achieve this end, organizations must have the ability to discover competent people with leadership qualities that promote better results in their work environment, as well as the use of strategies and mechanisms to develop more love (Tijjang et al, 2023), commitment (Grabowski et al, 2019;Tacadena and Muico, 2022;Mitonga-Monga et al, 2023) and ethics (Grabowski et al, 2019;Sakr et al, 2022;Tacadena and Muico, 2022), from employees to your organization.…”
Section: Introductionmentioning
confidence: 99%
“…Today, there are few studies carried out to predict the general health of employees within the workplace (Shi et al, 2022), in a post-COVID context where various jobs are carried out from the homes of employees; and it is here where there is a greater need to evaluate the changes in the general health of workers for the education sector. On the other hand, important scientific evidence shows that the practice of the leadership style of bosses/directors/managers has a significant impact on the health of workers (Sakr et al, 2022;Tinella et al, 2022;McKimm et al, 2023). Although it is true, the transformational leadership is an affective and high-profile leadership style, which is why many institutions disseminate and practice it (Miao and Cao, 2019), however, servant leadership has become one of the most studied, admired, disseminated and useful in various business sectors, due to the variety of benefits it produces (Kaltiainen and Hakanen, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It seems that the pandemic has exacerbated pre-existing inequalities. Members of wealthier families as well as people already having digital expertise or access to specialized technological assistance had better outcomes in comparison to less privileged ones, in terms of their learning goals, well-being and mental health [ 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…A series of meta-analyses [ 33 ] demonstrated that problem-focused coping is positively associated with health, indicating that efforts to solve the problem characterize individuals who report adaptive health behaviors. It has been found that active forms of coping have a positive effect on people’s health, whereas avoidance has the opposite effect [ 34 , 35 ]. Likewise, highly resilient people tend to engage in active solutions [ 36 ], and largely choose problem-focused coping [ 37 ].…”
Section: Introductionmentioning
confidence: 99%